Lidocaine constant rate infusion in isoflurane anesthetized neonatal foals - Lambertini, Carlotta; Spaccini, Francesca; Mazzanti, Alessia; Spadari, Alessandro; Lanci, Aliai; Romagnoli, Noemi (Frontiers in Veterinary Science, 2024)
In horses, lidocaine infusion is administered intraoperatively for analgesia and for a reduction of inhalant anaesthetic requirement. The objective of the study was to describe the anaesthetic effects of lidocaine infusion in isoflurane anaesthetised foals. The study was designed as a prospective clinical trial with an historical control group. Twelve foals (<3 weeks old) undergoing surgery were included in the study (LIDO group). Foals were premedicated with midazolam and butorphanol IV, anaesthesia was induced with ketamine and propofol IV and maintained with isoflurane. Lidocaine was administered intraoperatively at 0.05 mg/kg/min. Also, the anaesthetic records of 11 foals in which lidocaine was not administered intraoperatively were retrospectively evaluated and they were considered as a historical control group (HC). Heart rate (HR), mean arterial pressure (MAP) and fraction of expired isoflurane were monitored continuously. Time of extubation, time to reach sternal recumbency and standing were recorded. The quality of recovery was assessed. No differences were found between the groups for age, body weight, sex, breed, diagnosis, length of anaesthesia. HR decreased in both groups if compared with baseline values and intraoperatively the differences were statistically significant (p= 0.0102 and p= 0.03004 respectively in the LIDO and HC groups). Intraoperatively the HR was significantly lower in the LIDO group (71.2 ± 13.4 bpm) compared with the HC group (87.1 ± 17.7 bpm) (p= 0.0236). The number of foals requiring inotropic support (LIDO n=7 and HC n= 9) was not statistically associated with the treatment group (p= 0.371p= 0.2). The extubation time, the time to reach the sternal recumbency and the quality of recovery did not differ significantly between the two groups (p = 0.7 and p = 0.6 respectively). In conclusion, in anaesthetised foals the addition of lidocaine does not provide a sparing effect on isoflurane requirement, but it does not also provide a significant effect on the cardiovascular parameters and it does not interfere with the quality of recovery, however it decreases significantly the HR, which is pivotal in foals for the maintenance of cardiac output and peripheral perfusion. Therefore, a continuous patient monitoring is essential..